Catalytic Activity and Impedance Behavior of Screen‐Printed Nickel Oxide as Efficient Water Oxidation Catalysts. Issue 24 (30th November 2015) - Singh, Archana; Fekete, Monika; Gengenbach, Thomas; Simonov, Alexandr N.; Hocking, Rosalie K.; Chang, Shery L. Y.; Rothmann, Mathias; Powar, Satvasheel; Fu, Dongchuan; Hu, Zheng; Wu, Qiang; Cheng, Yi‐Bing; et al.
Abstract: We report that films screen printed from nickel oxide (NiO) nanoparticles and microballs are efficient electrocatalysts for water oxidation under near‐neutral and alkaline conditions. Investigations of the composition and structure of the screen‐printed films by X‐ray diffraction, X‐ray absorption spectroscopy, and scanning electron microscopy confirmed that the material was present as the cubic NiO phase. Comparison of the catalytic activity of the microball films to that of films fabricated by using NiO nanoparticles, under similar experimental conditions, revealed that the microball films outperform nanoparticle films of similar thickness owing to a more porous structure and higher surface area. A thinner, less‐resistive NiO nanoparticle film, however, was found to have higher activity per Ni atom. Anodization in borate buffer significantly improved the activity of all three films. X‐ray photoelectron spectroscopy showed that during anodization, a mixed nickel oxyhydroxide phase formed on the surface of all films, which could account for the improved activity. Impedance spectroscopy revealed that surface traps contribute significantly to the resistance of the NiO films. On anodization, the trap state resistance of all films was reduced, which led to significant improvements in activity. In 1.00 m NaOH, both the microball and nanoparticle films exhibit high long‐term stability and produce a stable current density of approximately 30 mA cm −2 at 600 mV overpotential. Abstract : A WOC in the park : Thin films of NiO nanoparticles and microballs are demonstrated to be efficient and highly robust water oxidation catalysts. Under similar experimental conditions, the microball films outperform the nanoparticle films of similar thickness owing to a more porous structure and higher surface area. Their performance improves with anodization as a result of the formation of a mixed nickel oxyhydroxide phase on the surface of the films.